Protocols and self-checking plans for the safety of post-COVID-19 balneotherapy - Clementi, Massimo; Signorelli, Carlo; Romano Spica, Vincenzo; Vitali, Matteo; Conti, Marco; Vitale, Marco (Acta Biomedica Atenei Parmensis, 2020)
During the COVID-19 pandemics, balneotherapic establishments were closed in Italy like in the rest of Europe. The Italian Foundation for Research in balneotherapy (FoRST) was asked to prepare a safety protocol to be proposed to the National Health Authorities to allow the establishments to restart their activity when possible, under safe conditions (the so-called Phase-2). The group of experts proposed the following hygienic and sanitary protocols of risk management for the initial reopening of the balneology settings in Italy. The plan aims to define the operating procedures to be implemented at the balneology establishments for the beginning of Phase-2 and to keep them constantly updated in the different periods that will characterize Phase-2 in relation to the trends of the disease. To this end the procedures, defined on the basis of the scientific state-of-the-art available today, will be updated and revised from time to time whenever further scientific evidence and directives from the Health Authorities make it necessary and/or useful.